Biomaterials For Craniofacial Bone Regeneration - Thrivikraman, Greeshma (Dent Clin North Am, 2017)
Functional reconstruction of craniofacial defects is a major clinical challenge in craniofacial sciences, especially in complex situations involving traumatic injury, cranioplasty and oncologic surgery. The advent of biomaterials has been viewed as a potential alternative to standard autologous/allogenic grafting procedures to achieve clinically successful bone regeneration. Over the years, the field of biomaterials for bone augmentation has swiftly advanced to create novel instructive materials and engineering technologies, emerging as an important therapeutic modality for craniofacial regeneration. This chapter discusses various classes of biomaterials, ranging from bioceramics to biopolymers that are currently employed in craniofacial reconstruction. Further, here we review the clinical applications of biomaterials as delivery agents for the sustained release of stem cells, genes and growth factors. Additionally, we cover recent advancements in 3D printing and bioprinting techniques that appear to be promising for future clinical treatments for craniofacial reconstruction. In summary, the present review highlights relevant topics in the bone regeneration literature exemplifying the potential of biomaterials to repair bone defects.